Pengaruh Penggunaan Sarana Produksi Terhadap Pendapatan Usahatani Jagung (Zea mays L.) (Kasus : Desa Sei Mencirim, Kec. Sunggal, Kab. Deli Serdang) - Hakim, Mukti; Lisdayani, Lisdayani (UNIVERSITAS LABUHANBATU, 2022)
Currently, the demand for corn in Indonesia is quite large, which is more than 10 million tons of dry shells per year. The largest consumption of corn is for the food and animal feed industry, because as much as 51% of the raw material for animal feed is corn. To increase the amount of production must be influenced by several factors. One of the main factors is the use of appropriate production facilities. Agricultural production facilities are all types of agricultural equipment, equipment and facilities that function as the main or auxiliary tools in the implementation of agricultural production. Production facilities play an important role in achieving production in accordance with the desired goals. The purpose of this study was to analyze the availability of agricultural production facilities in Sunggal District, Deli Serdang Regency. The research area was determined by purposive sampling, namely deliberately based on certain considerations and objectives in Sei Mencharim Village, Sunggal District, Deli Serdang Regency, which is a corn production area. Research from October to December 2021. The results of the multicollinearity assumption test, it can be seen that the means of production of Seeds (X1) has a VIF value of 4.113 which is smaller than 10, Fertilizer (X2) has a VIF value of 1.983 which is smaller than 10, and Pesticides ( X3) has a VIF value of 4.130 which is smaller than 10. The tolerance value of the Seed production facility (X1) has a tolerance value of 0.243 which is greater than 0.1, Fertilizer (X2) has a tolerance value of 0.504 which is greater than 0, 1, and Pesticides (X3) of 0.242 which is greater than 0.1. 2. The average total production costs incurred by corn farmers in one planting season with a land area of 1 ha is Rp 19,440,440, revenue is Rp 35,641,406 and income is Rp 16,200,966.Â Keywords : production facilities, farming, corn